Yoga-induced uveitis glaucoma hyphema syndrome - Mammo, Danny (Digit J Ophthalmol, 2020)
A 74-year-old pseudophakic white woman with pseudoexfoliation syndrome presented with right eye pain and photophobia and was found to have pseudophacodenesis with recurrent episodes of anterior uveitis, microhyphema, and elevated intraocular pressure (IOP). All episodes occurred after yoga sessions with intensive facedown postures. Ultrasound biomicroscopy (UBM) performed in supine and prone positions demonstrated significant change in the lens-bag complex position, with lens-iris touch. The patient underwent intraocular lens (IOL) explantation, anterior vitrectomy, and flanged intrascleral haptic-fixated IOL placement via double-needle technique, with resolution of all symptoms.